2014
DOI: 10.1016/j.wasman.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the composition of the initial mixtures on the chemical composition, physicochemical properties and humic-like substances content of composts

Abstract: The influence of the proportion of C-and N-rich raw materials (initial C/N ratio) and bulking agent on the chemical functional groups composition, humic-like substances (HS-like) content and physicochemical properties of composts was assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…In the present research, a significant increase in these four humification indices was found in both composts when composting ended, which indicated that the BSCM composts were evolving towards maturity under the influence of the environmental conditions prevailing during the composting process . Results from the current study are comparable with those of Silva, who reported similar values in the above‐mentioned humification indices. When the composting ended, the Treatment showed markedly higher levels of DP and PHA, about 0.46 and 27.50, compared with the CK (0.39 and 22.53) ( P < 0.05).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In the present research, a significant increase in these four humification indices was found in both composts when composting ended, which indicated that the BSCM composts were evolving towards maturity under the influence of the environmental conditions prevailing during the composting process . Results from the current study are comparable with those of Silva, who reported similar values in the above‐mentioned humification indices. When the composting ended, the Treatment showed markedly higher levels of DP and PHA, about 0.46 and 27.50, compared with the CK (0.39 and 22.53) ( P < 0.05).…”
Section: Resultssupporting
confidence: 87%
“…However, humic substances also consist of a hydrophilic fraction (HyI), which is usually more easily degraded and paid far less attention. In addition, the organic matter changes during composting vary significantly with feedstock from different sources . There have been no reports with respect to the spectroscopic characteristics of humic fractions (HA, FA and HyI) during BR composting.…”
Section: Introductionmentioning
confidence: 99%
“…Compulsory ventilation was at the rate of 0.5 L min -1 . The whole time of the experiment was conducted 50 days and the samples collected on day 0, 8,16,20,24,28,32,38,44 and 50. Six subsamples were removed from six sites of the entire profile spanning the whole profile (from top to bottom).…”
Section: Composting Testmentioning
confidence: 99%
“…It is reasonable for increasing the C/N ratio and pH to promote the production of HS because the HS is the alkaline compound of high carbon content(Silva et al, 2014). Band 5 and 14 were commonly found in a variety of materials composting, suggesting that the main function of these bacteria may be related to the aggregation of substance.…”
mentioning
confidence: 99%
“…Numerous studies have used different bulking agents, which are mostly from agriculture byproducts. They include sawdust (Martin et al 1993;Blanco and Almendros 1995;Banegas et al 2007;Adhikari et al 2008;Chang and Chen 2010;Yang et al 2013), wheat straw (Blanco and Almendros 1995;Banegas et al 2007), hay and pine wood shaving (Banegas et al 2007), bagasse and paper (Adhikari et al 2008), rice husk and rice barn (Chang and Chen 2010), wooden palette (Huet et al 2012), cornstalks and spent mushroom substrate (Yang et al 2013), wheat flour (Silva et al 2014), peat (Mathur et al 1986;Mathur et al 1990;Martin et al 1993;Vuorinen 2000;Nolan et al 2011), and barley straw (Vuorinen 2000).…”
Section: Introductionmentioning
confidence: 99%